Peran Guru dalam Mengembangkan Bahasa Lisan dan Tulisan Anak Usia Dini di RA Labschool IAIS Sambas - Saripah Saripah (Lembaga Pengembangan Kinerja Dosen, 2024)
This research discusses the role of teachers in developing the spoken and written language of early childhood at RA Labschool IAIS Sambas. Early childhood is an important period in language development. In this phase, children learn not only to speak verbally but also begin to recognize letters and numbers. The role of teachers in developing spoken and written language in early childhood is very vital. Teachers have the responsibility to create an environment that supports children's language development, both verbally and in writing. As a result of this research, researchers found that the role of teachers is very important in developing oral and written language skills in early childhood, including developing fine motor skills, understanding letter concepts, and the ability to compose words or sentences.